Ocorrência de pragas na cultura do algodão transgênico (bt) e convencional cultivado no sistema adensado e não-adensado - Romano, Daniele [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The cotton crop presents a complex of pests that can provide damage to the productivity and fiber quality. The narrow row cotton cultivation is different of the conventional space system, by having a larger number of plants in the same area, obtain greater precocity in the cotton cycle, with a cotton ready for harvest in 150 days, with a lower production cost, but can also occur impact on the occurrence and management of the insects. In Brazil cotton resistant to lepidopteran insects, Bollgard I (Bt), was introduced in 2005. The objective of this study was to evaluate the occurrence of pests in transgenic crop (Bt) and non-Bt growing in the conventional and narrow row cotton in the region of Primavera do Leste - MT, conducted at the 2nd harvest crop year 2010, in the Mato Grosso Experimental Cotton Institute- IMAmt. The treatments were evaluated weekly in order to verify the fluctuation of the major pests of cotton throughout the cycle. Monitoring of pests were being in 10 plants per plot, counting arthropods and separating them by species and obtained the rate of infestation and then decide to spray. Even also the percentage of defoliation caused by the caterpillars was evaluated. Based on these results it was concluded that: treatments with Bt (NuOpal) had the lowest incidence of Alabama argillacea, Pseudoplusia includens than non-Bt cultivar which was not observed for the species Spodoptera eridanea. Bt cultivar had lower percentage of defoliation caused by the caterpillars. The conventional cultivar (DeltaOpal) have had more percentage defoliation in narrow row cotton cultivation as the conventional space system, while cultivating Bt (NUOPAL) did not differ in the percentage defoliation, regardless of the spacing adopted. The narrow row cotton cultivation produced significantly more of the conventional space system and treatments with insecticide application kept the crop yield potential.

A cultura do algodoeiro apresenta um complexo de pragas que podem proporcionar danos na produtividade e qualidade da fibra. O sistema adensado de cultivo se diferencia do sistema de semeadura não-adensado por ter um maior número de plantas na mesma área, obtendo maior precocidade no ciclo, com colheita em até 150 dias, com menor custo de produção, podendo também ocorrer impacto na ocorrência e manejo de insetos. No Brasil o algodão com resistência a insetos lepidópteros Bollgard I (Bt) foi introduzido em 2005. O objetivo deste trabalho foi avaliar comparativamente a ocorrência de pragas na cultura do algodão transgênico (Bt) e não-transgênico (NBt) cultivado no sistema adensado e não-adensado, na região de Primavera do Leste – MT, conduzido na 2ª Safra do ano agrícola 2010, no Campo Experimental do Instituto Mato Grossense do Algodão – IMAmt. Os tratamentos foram avaliados semanalmente, visando verificar a flutuação das principais pragas ao longo do ciclo do algodão. O monitoramento das pragas foi realizado em 10 plantas ao acaso por parcela, contando-se os artrópodes, separando-os por espécie e obtido o índice de infestação das pragas para tomada de decisão de pulverizações. Avaliou-se também a porcentagem de desfolha provocada pelas lagartas. Pela análise dos resultados concluiu-se que: os tratamentos com a cultivar Bt (NuOpal) apresentaram as menores incidências de lagartas de Alabama argillacea e Pseudoplusia includens em relação a cultivar não-Bt, o que não ocorreu para a espécie Spodoptera eridanea. A cultivar Bt, obteve menor percentual de desfolha provocadas pelas lagartas. A cultivar convencional (DeltaOpal) sofreu mais desfolha no sistema de cultivo adensado que no cultivo não-adensado, enquanto que a cultivar Bt (NuOpal) não diferiu no percentual de desfolha, independente do espaçamento adotado. O sistema de cultivo adensado produziu significativamente mais algodão em caroço que o ...
Keywords: Algodão - Doenças e pragas - Controle; Algodão - Espaçamento; Pragas agricolas; Inseticidas; Agricultural pests Control